KURVA PENAWARAN TENAGA KERJA DAN JAM KERJA PEREMPUAN - Mawadah, Sokhikhatul (Sawwa: Jurnal Studi Gender, 2017)
The labor supply curve is a curve that states the relationship of wages and hours of work. The higher a person's wages the fewer hours they work. The curve should not be appropriate if it is associated with women's working hours, because there are still many women who work a lot but pay little. Especially for women who work on households, how many hours work to work at home and work in the office. The purpose of this paper is to find out the relationship of wages and working hours of women, Analyzing the labor supply curve based on Central Java Provincial BPS data on women's working hours and knowing the relevance of the labor supply curve to the current (working women) society condition. From the discussion in this writing is known that many factors that affect the labor supply curve, one of which is the factor of women who take care of the household. So there is a relationship between the labor supply curve with female work hours but is less relevant. The labor supply curve does address wages and hours of work but does not deal specifically with wages, working hours and women. There should be a distinction or an exception to women. especially working hours of working women (as professions) with women who only work as housewives. let alone strengthened from the data of BPS statistics center agency which shows the number of working hours of women more than the number of man hours worked._________________________________________________________Kurva penawaran tenaga kerja adalah kurva yang menyatakan hubungan upah dan jam kerja. Semakin tinggi upah seseorang maka semakin sedikit jam kerjanya. Kurva tersebut tidak sepatutnya tepat jika dikaitkan dengan jam kerja perempuan, karena masih banyak perempuan yang jam kerjanya banyak tetapi upahnya sedikit. Apalagi untuk perempuan yang bekerja mengurusi rumah tangga, berapa banyak jumlah jam kerja untuk di bekerja di rumah dan bekerja di kantor. Tujuan penulisan ini adalah untuk mengetahui hubungan upah dan jam kerja perempuan, Menganalisa kurva penawaran tenaga kerja berdasarkan data BPS Provinsi Jateng tentang jam kerja perempuan dan Mengetahui relevansi kurva penawaran tenaga kerja dengan keadaan masyarakat (perempuan bekerja) dewasa ini. Dari pembahasan dalam penulisan ini diketahui bahwa banyak faktor yang mempengaruhi kurva penawaran tenaga kerja, salah satunya adalah faktor wanita yang mengurus rumah tangga. Jadi ada hubungan antara kurva penawaran tenaga kerja dengan jam kerja perempuan tetapi kurang relevan. Kurva penawaran tenaga kerja memang membahas tentang upah dan jam kerja tetapi tidak membahas spesifik tentang upah, jam kerja dan perempuan. Seharusnya ada pembeda/pengecualian terhadap perempuan, khususnya jam kerja perempuan yang bekerja (sebagai profesi) dengan perempuan yang hanya bekerja sebagai ibu rumah tangga. Apalagi dikuatkan dari data Badan Pusat Statistik (BPS) yang menunjukkan jumlah jam kerja wanita lebih banyak dibanding jumlah jam kerja laki-laki.